Performance | Katerine Duska | TEDxUniversityoftheAegean (TEDx UniversityoftheAegean, 2018)
: Καλησπέρα σας, ευχαριστούμε πάρα πολύ, χαιρόμαστε πολύ που είμαστε εδώ απόψε. Λοιπόν, θα ξεκινήσουμε με ένα τραγούδι μου που λέγεται «Somebody» και μιλάει για το πόσο ευάλωτος μας κάνει η αγάπη. [♪ vos, «Somebody» medley version « To get hung up on somebody, call on someone on you Voluntarily, in solitary Love is an idea, concept that simply outgrew Past the point of needing one's caress Hear me, I'm not looking to digress I know that you're trying to make me want somebody I've been tired, proven I don't need nobody While others fold the way they do Don't think that I will turn up to you Done it all before bread needs nowhere I won't tell you, won't reclaim for you all that he holds captive Innocence that he withdrew I know it pains you to try to tame you Defile your ideas and cloud your perfect skyline view Cause I once learned the hard way a heart makes May come full circle but still be turning I know that you're trying to make me want somebody I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Show me something, show me something There's something about you Show me something, show me something There's something about you Oh you say, give me something, give me something There's something around you Give me something, give me something There's something loving around you I know that you're trying to make me want somebody I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something about you Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody While others laugh the way they do Don't think that I will warm up to you Done it all before bread needs nowhere Oh you say, give me something, give me something There's something loving around you I've been tired, proven I don't need nobody One in a million Why, why can't I see it, tell me Why am I kneeling for your night One in a million Why, why can't I see it, tell me Why am I kneeling for your night One in a million Why, why can't I see it One in a million Why, why can't I see it, tell me Why am I kneeling for your night One in a million Τον καιρό που μ' αγαπούσες Μ' ερωτάς ένα πρωί Στην κουβέντα μας απάνω Την αράχη ζωή Τότε γύρισα και σου είπα Για άλλους είναι το κρασί Για άλλους δόξα, για άλλους πλούτη Μα για μένα είσαι εσύ Για άλλους δόξα, για άλλους πλούτη Μα για μένα είσαι εσύ Τώρα που άλλαξε η καρδιά σου Και έναν άλλον αγαπάς Απορίς μου λένε ακόμα Η δική μου πώς τυπά Μήπως τα χάσα και εμένα Δεν είναι άνθρωποι πολύ Από μέσα πέθαμενοι Και απόξω ζωντανοί Από μέσα πέθαμενοι Και απόξω ζωντανοί Τον καιρό που μ' αγαπούσες Με ρωτάς ένα πρωί Στην κουβέντα μας απάνω Την αραχή ζωή Τότε γύρισα και σου είπα Για άλλους είναι το κρασί Για άλλους δόξα, για άλλους πλούτη Μα για μένα είσαι εσύ Για άλλους δόξα, για άλλους πλούτη Μα για μένα είσαι εσύ Θα ήθελα να ευχαριστήσω πάρα πολύ το Terex, Adrian, για αυτή την πρόσκληση. Παιδιά, είστε πραγματικά υπερόχεια, αλήθεια. Είστε σπάνιες περιπτώσεις. Χαίρομαι πάρα πολύ που είμαι κι εγώ μέσα σε όλο αυτό. Θα ήθελα να παρουσιάσω τον κιθαρίστα μου και φίλο μου, Δημήτρη Στασινό. Αυτό λοιπόν λέγεται «Slow» Feels like it's time for reprise I know you wanna cut through all my ties I've been waiting long, I've been waiting long Dark like a heap of winter skies Reach for the sky, I'm locked in your eyes I've been waiting long, I've been waiting long Don't need to tell you I'm fine When all else has failed Cause we're drifting into depths I've known before When I get back to shining Desire is burning Won't you consider going slow, slow, slow Go on delayed, further, further, further I can't relate to slow, slow, slow I need you to go slow, slow, slow Even though our fates won't sympathize Post our hearts they'll symphonize I've been waiting long, I've been waiting long Don't need to tell you I'm frail Going down this trail Descending into depths I've known before When my guts are turning Where will I start learning? Won't you consider going slow, slow, slow Go on delayed, further, further, further I can't relate to slow, slow, slow I need you to go slow, slow, slow Oh, oh, oh Ah, ah, ah, ah Oh, oh, oh Ah, ah, ah Slow, slow, slow Slow, slow, slow Slow, slow, slow Slow, slow, slow Slow, slow, slow Go on delayed, further, further, further I can't relate to slow, slow, slow I need you to go slow, slow, slow Slow, slow, slow way Foul, foul, foul day Slow, slow I need you to go slow, slow, slow